POTRET OBJEK DAKWAH: Membuka Tabir Patrimonial Di Pulau Seribu Masjid - Nurul Hakim (TASÂMUH, 2016)
Many people misinterpret the democracy, and most of them also have not yet understood thoroughly what the democracy is. It is not doubtful many people rise up against, argue and want to replace the system of democracy with a particular government system. Whereas if it investigated more deeply, negative jargons issued by activists like capitalism, ocialism, democracy, materialism, liberalism, and secular, are the struggling process, a series of bloody history for socio-historical change, freedom from the restraint of patrimonial culture in the darkness era of Europe. This paper attempt to offer ideas that might berelevant to answer the challenge of social change in the future. Nationalism theory Elnest Gellner explains the process in realizing the ideal nation state, without tendency of ethnic, race, religion discrimination (SARA). His idea influenced by Max Weber, Durkheim, Karl max adopted the process and description of society change manifested from nomadic life, farming (low education),until industrial society with capitalism in the western Europe.